PENGARUH KEPERCAYAAN DIRI TERHADAP KEMAMPUAN PUBLIC SPEAKING DAN LEADERSHIP PADA ANGGOTA GENERASI BARU INDONESIA (GenBI) RIAU PERIODE 2021 - Selvia Yunisha; Nurjanah; Haryati (PROGRAM STUDI ILMU KOMUNIKASI, 2022)
ABSTRACT Self-confidence is an invaluable attribute in an individual in his social life. This is because with self-confidence, a person is able to actualize all his potential such as public speaking and leadership skills. GenBI Riau is a community of Bank Indonesia scholarship recipients in the Riau area. All members of GenBI Riau received special training, especially in the fields of public speaking and leadership. So the purpose of this study is to find out whether there is an influence of self-confidence on public speaking and leadership skills in members of the 2021 Riau New Generation (GenBI). This research uses quantitative method with a correlational approach. The population in this study was 331 members, then using the Slovin formula obtained a sample of 181 respondents. The sample determination technique used in this study is the proportionate random sampling technique. The data analysis technique uses simple linear regression and the coefficient of determination (R2). The data analysis techniques used can determine the measurement scale of each variable. The results of the study concluded that self-confidence had a positive effect of 45.8% on public speaking ability and on leadership by 43% on members of the Indonesian New Generation (GenBI) Riau in 2021.